Comparative floral anatomy in species of Cyperoideae (Poales: Cyperaceae) and insights into the evolution of floral traits - De Oliveira Silva, Lucimara Reis [UNESP]; Trevisan, Rafael; Oriani, Aline [UNESP] (Oxford University Press (OUP), 2023)
Species of Cyperoideae exhibit wide morphological variation in their flowers due to reduction processes. Their flowers can be bisexual or unisexual, achlamydeous or not, with tepals and stamens varying from one to six and a trimerous or dimerous gynoecium, the latter dorsiventrally or laterally flattened. We studied the floral anatomy and vasculature of Fuirena robusta, Cyperus sesquiflorus, Rhynchospora panicoides, and Schoenoplectus californicus to understand the reduction processes that resulted in different floral morphologies. The floral development of C. sesquiflorus was also analysed. All these species have spikelets with bisexual flowers, but they vary in relation to the perianth, androecium, and gynoecium. Our results show the loss of the outer abaxial tepal in R. panicoides, the total loss of the outer whorl of tepals in F. robusta, and the loss of abaxial tepals (outer and inner) in S. californicus. The tepals are vascularized in F. robusta and R. panicoides and non-vascularized in S. californicus. In C. sesquiflorus, the perianth is absent. Phenolic compounds present in the epidermal cells of the receptacle mark the boundaries between tepals and stamens, before the individualization of these parts. The three stamens present in F. robusta and R. panicoides correspond to the outer whorl. In S. californicus, there is a loss of the adaxial stamens (outer and inner), whereas in C. sesquiflorus the outer stamen whorl and the inner adaxial stamen are lost. The laterally flattened dimerous gynoecium in C. sesquiflorus may be the result of the pressure exerted by the distichously arranged glumes. The most distal flower of the spikelet in this species is staminate by abortion of the gynoecium. The morphological diversity observed in the flowers of Cyperoideae is the result of distinct reduction processes that probably occurred independently in the different clades of the subfamily during the evolution of Cyperaceae.
Keywords: floral anatomy; floral development; gynoecium; perianth; reduction; stamen